Characterising applied forces during positive pressure ventilation: a randomised cross-over simulation study - Gary Weiner; Jacqueline Hannan; Leia Stirling (BMJ Publishing Group, 2024)
Objective To characterise applied force on the face and head during simulated mask ventilation with varying mask, device and expertise level.Design Randomised cross-over simulation study.Setting A quiet, empty room in the children's hospital.Participants Neonatal healthcare providers, categorised as novices and experts in positive pressure ventilation (PPV).Interventions PPV for 2 min each in a 2×2 within-subjects design with two masks (round and anatomic) and two ventilation devices (T-piece and self-inflating bag (SIB)).Main outcome measures Applied force (Newton (N)) measured under the head and at four locations on the manikin's face (nasal bridge, mentum, left and right zygomatic arches) and symmetry of force applied around the mask rim.Results For the 51 participants, force applied to the head was greater with the SIB than the T-piece (mean (SD): 16.03 (6.96) N vs 14.31 (5.16) N) and greater with the anatomic mask than the round mask (mean (SD): 16.07 (6.80) N vs 14.26 (5.35) N). Underhead force decreased over the duration of PPV for all conditions. Force measured on the face was greatest at the left zygomatic arch (median (IQR): 0.97 (0.70-1.43) N) and least at the mentum (median (IQR): 0.44 (0.28-0.61) N). Overall, experts applied more equal force around the mask rim compared with novices (median (IQR): 0.46 (0.26-0.79) N vs 0.65 (0.24-1.18) N, p<0.001).Conclusion We characterised an initial dataset of applied forces on the face and head during simulated PPV and described differences in force when considering mask type, device type and expertise.